Effect of Snakebite on Osteomyelitis and Cardiac Shock in Pediatric and Adult Patients - R. Mohamad Javier; Laksmitha Saktiono Safitri; Andisa Fadhila Rialdi; Ehwanul Handika; Ericko Julian Limanto; Budi Prakoso; Bambang Widiwanto; Himawan Wicaksono; Zainuddin Hamidi; Djanuar Fitriadi; Sukirman Sukirman (Journal of Social Research, 2023)
Snakebite is a defense mechanism of snakes and can be a medical emergency. Snake venom contains a mixture of protein components that affect the functional activity of the target physiology. The structure of the poison in snake venom has different variations for different snake species. As for snakebite, it can be life-threatening if it has neurotoxic, cytotoxic, or hemotoxic toxic effects. The purpose of this study is to determine the relationship between snakebite incidence to osteomyelitis and cardiogenic shock. The results of this study can be used as a source of information and an objective correlation reference regarding the relationship between snakebite and osteomyelitis and cardiogenic shock. This research is a Systematic Review using the Preferred Reporting Items for Systematic Reviews and Meta-analyses method or commonly called PRISMA, this method is carried out systematically by following the correct research stages or protocols. Antivenom neutralizes toxins in fixed quantities. Both children and adults are given the same amount of antivenom because snakes inject the same amount of poison into both adults and children. Antivenom can be effective as long as the poison is still active in the patient's body causing symptoms of systemic intoxication. It can last for several days or even weeks after the bite. After a series of processes have been passed, based on the results of research in the Scopus-indexed journal on the systematic "The Relationship of Snakebite with Osteomyelitis and Cardiac shock in Pediatric and Adult Patients" a conclusion can be drawn, namely that the majority of journals discuss heart disorders and infections, necrosis of muscles and bones related to poisonous snake bites.